Effects of Supply Chain Management on Tourism Development by using Smart Security Methods: A Case Study of Shanghai - Abili, Maryam; Zhao, Yan (ExcelingTech, 2019)
The paper aims to investigate the possible relationship between Tourism Supply Chain and Strategic Partnership, read as a way to reduce and better manage the complexity in Tourism Industry. For this purpose weexamined creating tourist security using a smart wristband for Shanghai tourists. The sampling method is simply random and via Cochran’s formula. The sample size is 300 people. All questions have been used in the form of Likert Scale for data collection. The content validity and Cronbach’s alpha coefficient have been used to determine the survey validity, which equals 0.91. LISREL software has been used for data analysis and hypothesis testing. Results showed that using technology (wristband) and the tourist police are effective in the development of tourism and improved tourism facilities.